Reproductivity of captive wild bactrian camels (camelus, przewalskii, 1878) - G, Dovchindorj; Baoyin, Taogetao; Minggagud, Hugjiltu; G, Ariunjargal; B, Munkhtsog (Mongolian Journal of Agricultural Sciences, 2018)
Wild camel is the endangered native species of Central Asia that are found only in the western north of China, and Trans Altai Gobi of Mongolia. In this article was written that the reproductivity of captive wild bactrian camels based on the result and analysis developed at the research center for “Captive Wild camel breeding center”located near administration of Great Gobi Strictly Protected Area “A” part, between 1992 -2015. A gestation age, birth repetition and birth time of female captive wild camels at the breeding center under semi-captive condition have been observed and analysed. According to the research, captive wild camel birth time is started from the last 10 days of March and it finished at the last 10 days of May. Most extensive birth time is April. Captive male wild camel at the breeding center starting to mate at the beginning of January, and finished at the end of February. Therefore, an average gestation period of captive female camels is 400-440 days. However, sometimes, it can fluctuated due to age, fattening, and climate condition. But also birth date of female camels may different because of sex of calf.